Detection of complement-fixing antiphospholipid antibodies in association with thrombosis - Munakata, Y; Saito, T; Matsuda, K; Seino, J; Shibata, S; Sasaki, T (Thrombosis and haemostasis, 2000)
Antiphospholipid antibody (aPL) is a hallmark of antiphospholipid syndrome (APS), characterized by thrombosis and recurrent fetal loss. We developed a novel ELISA system to detect complement-fixing ability of anticardiolipin antibody (aCL), and evaluated its clinical usefulness through studying the prevalence of the antibodies in rheumatic diseases, especially in association with thrombosis and recurrent abortion. Among 189 patients with rheumatic diseases, the complement-fixing aCL was positive in 26 (83.9%) of 31 patients with APS and 2 (1.3%) of 158 with other disease categories, whereas it was not positive among 52 normal subjects. Twenty-seven of 28 patients (96.4%), who were positive for complement-fixing aCL, had the episodes or history of thrombosis and/or recurrent abortion, at the time we studied. The remaining one in this group developed APS manifesting pulmonary infarction and occlusion of mesenteric artery 6 months after the evaluation. The sensitivity and specificity of this assay system were 75.0% and 99.3%, respectively, in relation with thrombotic episodes. On the other hand, the IgG aCL were positive in 28 (77.8%) of 36 cases with recent thrombotic episodes and 24 (15.7%) of 153 cases with no recent thrombotic episodes. The sensitivity and specificity of IgG aCL assay system were 77.8% and 84.3%, respectively, in relation with thrombotic episodes. These results indicate that complement-fixing aCL may specifically occur in association with the episodes of thrombosis and/or recurrent abortion in patients with APS compared to IgG-aCL. The method for detecting the complement-fixing aCL is simple, and it provides the useful diagnostic marker for thrombotic manifestations associated with APS.